(untitled) (Historia, 2021)
Perhaps one of the most admirable characteristics of Mr. Steytler washis zest for history. He approached it with a gusto that is unfortunatelyall too rare and one recalls his excited summons of "Kom kyk hierso!"when he unearthed a humorous item or document of significance amongthe archival records or his triumphant return from the battlefield ofUlundi with old cartridge cases and fragments of shells. In the veldwhich he loved, he had a keen eye and an uncanny instinct for turning upi resting relics. He capped a life of rich experience with illuminatinganecdotes and gave his colleagues and friends revealing glimpses of thepioneers of humble farm schools in the Free State and of those in highplaces whom he had known intimately, especially General Hertzog andMr. N. C. Havenga